'Signor Perugini' and advertising education in Australia. Issue 2 (3rd April 2019) - Dickenson, Jackie
Abstract: The Australian advertising industry took steps to improve its efficiency and reputation in the interwar period. These steps included restricting entry to the industry by means of a national accreditation system based on standardised courses and examinations. This article examines the development and application of this system by tracing the background and career of Edward Perugini, Australia's leading advertising educator and the architect of the industry's scheme. It finds that, under Perugini's guidance, the industry tempered its embrace of the 'science' of advertising – the dependence on research and sweeping psychological 'insights' – with attention to art in advertising, anticipating the 'Creative Revolution' of the late 1960s.